Synthesis, structural and spectroscopic studies of 2-oxoacenaphthylen-1(2H)-ylidene nicotinohydrazide - Henriques, M. S. C. (2017)
The synthesis of a new hydrazone, 2-oxoacenaphthylen-1(2H)-ylidene nicotinohydrazide, and its structural and spectroscopic characterization is reported. The obtained powder was recrystallized from DMSO and ethanol that afforded small crystals used for single-crystal X-ray diffraction studies. The compound was found to crystallize in two polymorphs, depending on the crystallization conditions. One of the polymorphs (form I) crystallizes in the centrosymmetric P21/c monoclinic space group, the other (form II) crystallizes in the non-centrosymmetric, but achiral, orthorhombic space group P212121. Conformation of the molecules is similar in both polymorphs, but the network of weak intermolecular interactions determining the crystal packing is different. In form II an additional C-H⋯O bond connects molecules related by the screw-axis running parallel to the a-axis. Crystals of both polymorphs were also screened by FT-IR and Raman microscopy; a detailed analysis of the spectra and comparison with those of the isolated molecule calculated by ab-initio HF/MP2 and DFT/B3LYP methods using a correlation consistent cc-pVDZ basis set is presented. In addition, UV-vis and NMR studies were performed in solution.